Miscarriages of transmission: body, text, and method. (September 2016) - Goodrich, P.
Abstract: An introductory and exploratory attempt to examine the possibility of viewing the famous writings of Judge Daniel Paul Schreber as the intimations of translawyering. Volubly convinced he was becoming a woman, Judge Schreber announced that he would nail his flag to the feminine and was incarcerated as mad for his pains and his pleasures. It is time to release him and to read his work not as madness but as a unique conjunction of desire and law.